Fulfillment of the Rights of Restitution for Child Victims of Sexual Crimes (Study of the Appeal Decision of the Bangka Belitung High Court Number 14/Pid.sus/2024/PT BBL) - Yuli Redha Rosalin; Junaidi Abdillah (Dinasti Research, 2024)
The aim to be achieved in this research is to find out about the fulfillment of the right to restitution for child victims of sexual crimes. The method used in this research is normative juridical where researchers use secondary legal materials originating from decisions as well as journals and books related to the research topic being conducted. The payment of restitution received by the victim in decision Number 14/PID.SUS/2024/PT BBL is a form of legal certainty for the victim where the essence of legal certainty is a form of implementation in which there is a law enforcement mechanism for various actions without any views who is the individual who broke the law.